THE EFFECT OF WORD OF MOUTH ON CONSUMER PURCHASING DECISIONS AT SHOPEE (ONLINE SHOP) IN PEKANBARU: Survey of 7th Semester Students of Economics Accounting Education, Faculty of Teacher Training and Education, Islamic University of Riau - Kiki Joesyiana (VALUTA, 2018)
This research was aimed to know, explain and analyze The Effect of Word of Mouth on Consumer Purchasing Decisions Through Shopee Media Online Shop in Pekanbaru, which survey was conducted on 7th semester students of Economics Accounting Education, Faculty of Teacher Training and Education, Islamic University of Riau. This study uses explanatory research withsurvey methodsthrough a quantitative approach. The population in the study is students as consumers who have used Shopee media online shop. It uses data collection methodof census because the number of respondents who are involved is low, which is 78 respondents. The method of data collection used is a questionnaire. Data analysis usesquantitative descriptive withsimple linear regression analysis formula processed using the SPSS 20 program. The results of this study indicate that: there is a significant effect between Word of Mouth on consumer purchasing decisions through Shopee media online shop in Pekanbaru.